INSTRuCT: Protocol, Infrastructure, and Governance. Issue 10 (October 2021) - Pandian, Jeyaraj Durai; Verma, Shweta Jain; Arora, Deepti; Sharma, Meenakshi; Dhaliwal, Rupinder; Khatter, Himani; Huilgol, Rahul; Sylaja, P.N.; Dhasan, Aneesh; Renjith, Vishnu; Pathak, Abhishek; Pai, Aparna; et al.
Abstract : Background and Purpose: Very few large scale multicentric stroke clinical trials have been done in India. The Indian Council of Medical Research funded INSTRuCT (Indian Stroke Clinical Trial Network) as a task force project with the objectives to establish a state-of-the-art stroke clinical trial network and to conduct pharmacological and nonpharmacological stroke clinical trials relevant to the nation and globally. The purpose of the article is to enumerate the structure of multicentric stroke network, with emphasis on its scope, challenges and expectations in India. Methods: Multiple expert group meetings were conducted by Indian Council of Medical Research to understand the scope of network to perform stroke clinical trials in the country. Established stroke centers with annual volume of 200 patients with stroke with prior experience of conducting clinical trials were included. Central coordinating center, standard operating procedures, data and safety monitoring board were formed. Discussion: In first phase, 2 trials were initiated namely, SPRINT (Secondary Prevention by Structured Semi-Interactive Stroke Prevention Package in India) and Ayurveda treatment in the rehabilitation of patients with ischemic stroke in India (RESTORE [Rehabilitation of Ischemic stroke Patients in India: A Randomized controlled trial]). In second phase, 4 trials have been approved. SPRINT trial was the first to be initiated. SPRINT trial randomized first patient on April 28, 2018; recruited 3048 patients with an average of 128.5 per month so far. The first follow-up was completed on May 27, 2019. RESTORE trial randomized first patient on May 22, 2019; recruited 49 patients with an average of 3.7 per month so far. The first follow-up was completed on August 30, 2019. Conclusions: In next 5 years, INSTRuCT will be able to complete high-quality large scale stroke trials which are relevant globally. REGISTRATION: URL: http://www.ctri.nic.in/ ; Unique Identifier: CTRI/2017/05/008507. Abstract : Supplemental Digital Content is available in the text.